2016
DOI: 10.1002/jssc.201600286
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction and quantification of albendazole and triclabendazole using vortex‐assisted hollow‐fiber liquid‐phase microextraction combined with high‐performance liquid chromatography

Abstract: A novel, simple, and rapid vortex-assisted hollow-fiber liquid-phase microextraction method was developed for the simultaneous extraction of albendazole and triclabendazole from various matrices before their determination by high-performance liquid chromatography with fluorescence detection. Several factors influencing the microextraction efficiency including sample pH, nature and volume of extraction solvent, ionic strength, vortex time, and sample volume were investigated and optimized. Under the optimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Salt addition might pose double effects on the LPME extraction efficiency of target analytes, such as decreasing the solubility of analytes and acceptor phase by salting‐out effect, reducing the diffusion coefficients of analytes . A mass of optimization experiments have showed that NaCl addition does not have an important effect on the LPME efficiencies of analytes such as ochratoxin , albendazole and triclabendazole , or even a considerable negative effect on the extraction efficiency of some pesticide residues in fruit and vegetable samples . Although the addition of salt such as saturated Na 2 SO 4 did increase the extraction efficiency of SAs , there was no further optimization of salt effect in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Salt addition might pose double effects on the LPME extraction efficiency of target analytes, such as decreasing the solubility of analytes and acceptor phase by salting‐out effect, reducing the diffusion coefficients of analytes . A mass of optimization experiments have showed that NaCl addition does not have an important effect on the LPME efficiencies of analytes such as ochratoxin , albendazole and triclabendazole , or even a considerable negative effect on the extraction efficiency of some pesticide residues in fruit and vegetable samples . Although the addition of salt such as saturated Na 2 SO 4 did increase the extraction efficiency of SAs , there was no further optimization of salt effect in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement factor (EF) and extraction recovery (ER) of the developed microextraction method were calculated by the following equations: EF 0.33em=mamw ER %= EF 0.33em×V organic V aqueous ×100where m a , m w , V organic , and V aqueous are the slope of calibration graph after extraction of OTA by the developed method, the slope of calibration graph without extraction of OTA, the volume of the organic extractant, and the volume of the aqueous sample, respectively .…”
Section: Methodsmentioning
confidence: 99%
“…LPME as a miniaturized application of LLE has rapid, low cost, and simple procedure. LPME has several modes including single drop microextraction , hollow fiber LPME , dispersive liquid‐phase microextraction (DLPME) , and solidified floating organic drop (SFOD) microextraction .…”
Section: Introductionmentioning
confidence: 99%
“…In HF‐LPME method, analytes are extracted from aqueous donor phase into organic phase by an organic solvent immobilized in the porous wall of hollow fiber . Large molecules cannot permeate through the pores of hollow fiber wall, thereby allows the HF‐LPME method to have such excellent clean‐up efficiency . In addition, its other advantages, including high enrichment factor, required negligible volume of solvents, and low cost, also promote this method to be a promising and reliable extraction technology in the sample preparation field .…”
Section: Introductionmentioning
confidence: 99%